Cross-talk between the cytokinin, auxin, and gibberellin regulatory networks in determining parthenocarpy in cucumber - Mandal, Neha Kumari; Kumari, Khushboo; Kundu, Aditi; Arora, Ajay; Bhowmick, Prolay K.; Iquebal, Mir Asif; Jaiswal, Sarika; Behera, Tusar Kanti; Munshi, A. D.; Dey, Shyam S. (Frontiers in Genetics, 2022)
Cucumber is a model plant to study parthenocarpy with abundant slicing and pickling type germplasm. This study was undertaken to understand the role of important cytokines (CKs), auxin (AUX) and gibberellin (GA) biosynthesis and degradation genes for induction of parthenocarpy in slicing and pickling germplasm. Two genotypes of gynoecious parthenocarpic cucumber, PPC-6 and DG-8 along with a MABC derived gynoecious non-parthenocarpic line, IMPU-1 were evaluated under this study. The slicing and pickling cucumber genotypes, PPC-6 and DG-8 were strong parthenocarpic in nature and set fruits normally without pollination. Endogenous auxin and gibberellin were significantly higher in parthenocarpic as compared to non-parthenocarpic genotype whereas concentration of cytokinins varied among the genotypes at different developmental stages. However, exogenous application of Zeatin and IAA + Zeatin were effective in induction of parthenocarpic fruits in IMPU-1. Expression analysis with important CK, AUX and GA biosynthesis related genes were studied in IMPU-1, PPC-6 and DG-8. Expression of the CK synthase, IPT, IPT3, PaO, LOG1, LOG2, CYP735A1 and CYP735A2 were upregulated in the parthenocarpic genotypes. Among the transcription factors-response regulators (RRs), positive regulation of the CSRR8/9b, CSRR8/9d, CSRR8/9e and CSRR16/17 in the parthenocarpic lines and negative feedback of the CK signalling genes, such as CsRR3/4a, CsRR3/4b, CsRR8/9a, and CsRR8/9c were recorded. Homeostasis between cytokinin biosynthesis and degradation genes like CK oxidases (CKXs), CK dehydrogenase resulted in non-significant difference in the endogenous CK concentration in the parthenocarpic and non-parthenocarpic genotypes. Besides, upregulation of the key auxin inducing proteins and GA biosynthesis genes indicated their crucial role in parthenocarpic fruit set of cucumber. This study establishes the critical role of the CKs, AUX and GA regulatory networks and their cross-talk in determining parthenocarpy in slicing and pickling cucumber genotypes.